2021
DOI: 10.3390/agronomy11091819
|View full text |Cite
|
Sign up to set email alerts
|

Early and Total Yield Enhancement of the Globe Artichoke Using an Ecofriendly Seaweed Extract-Based Biostimulant and PK Fertilizer

Abstract: This study evaluated the effect of phosphorus and potassium (PK) fertilizer levels and foliar seaweed extract on early and total yield productivity and the growth of globe artichoke plants. Field experiments were conducted over two seasons on loamy–clay soil at the vegetable research farm, of the Faculty of Agriculture, Alexandria University, Egypt. Fertilizer levels of 0, 25, 50 and 75 mL L−1, and seaweed extract concentrations of 0, 5 and 10 mg L−1, individually and in combination, were used. Globe artichoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…Fertilizing globe artichoke plants with 75% of the recommended NPK provided the highest values of plant height in both seasons. Similar findings from Selim (2019) demonstrated that adding 75% NPK significantly enhanced the height of potato plants and (Elsharkawy et al, 2021) who found that treated artichoke with 75% of requisite P and K increased the plant height. On the contrary, (Petropoulos et al 2022) found that the maximum plant height was produced with adding 100% of recommended potassium for globe artichoke plants.…”
Section: Growth Parameters Plant Heightsupporting
confidence: 80%
See 1 more Smart Citation
“…Fertilizing globe artichoke plants with 75% of the recommended NPK provided the highest values of plant height in both seasons. Similar findings from Selim (2019) demonstrated that adding 75% NPK significantly enhanced the height of potato plants and (Elsharkawy et al, 2021) who found that treated artichoke with 75% of requisite P and K increased the plant height. On the contrary, (Petropoulos et al 2022) found that the maximum plant height was produced with adding 100% of recommended potassium for globe artichoke plants.…”
Section: Growth Parameters Plant Heightsupporting
confidence: 80%
“…K is essential for sugar translocation and the synthesis of carbohydrates because potassium ion is known to be one of the three largest constituents in sieve tube sap (Moussa, 2011). Increasing rates of potassium and phosphorus fertilizers had positive effect on the inulin content of artichoke heads (Elsharkawy et al,2021). Related results were obtained by (Petropoulos et al, 2022) who indicate that applied 75% of recommended dose K significantly increased the inulin content.…”
Section: Chemical Components Dry Matter (%)supporting
confidence: 63%
“…Several authors have investigated alternative and innovative crop management strategies to increase the globe artichoke yield productivity, by adopting different fertilization rates (Ierna et al. , 2012a, 2012b), using biostimulant (Elsharkawy et al. , 2021) and organo-mineral (Ierna and Mauromicale, 2013), caring the seasonality (Ierna et al.…”
Section: Discussionmentioning
confidence: 99%
“…i.e., auxins (IAA and IBA), cytokinins, vitamins, enzymes and amino acids (Khan et al, 2009). Stress resistance has been demonstrated to be improved by using seaweed extracts and improving yield in many other crops, such as Celeriac Plant (Shehata et al, 2011) common bean, (Zewail, 2014), spinach (Xu and Leskovar, 2015), also, in this regard, plants sprayed with algae extract enhanced growth characters, e.g., plant height, numbers of leaves, leaves area, fresh and dry weight of shoot, yield and its components on Globe Artichoke (Sayed et al, 2018;Madian et al,2020;Elsharkawy., et al, 2021), on sweet potato (Helaly, 2021), on tomato (Hussain et al, 2021), on potato (Negm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%